MODELLING GROWING SPACE FOR ARAUCARIA - Costa, Emanuel Arnoni (2018)
This study was developed in order to model the growing space for Araucaria angustifolia (Bertol.) Kuntze trees. A total of 869 Parana pine trees were sampled in three municipalities in southern Brazil, being 175 trees with free growing of competition in the municipalities of Canoinhas (SC state) and Lages (SC state), and 694 under influence of competition in natural forest in the municipalities of São Francisco de Paula (RS state) and Lages (SC state). In each tree was measured diameter at breast height, total height and crown rays following the directions of the cardinal points. The crown diameter was determined by doubling the value of the average radius of the crown. Three models were fitted and evaluated the fit statistics, accuracy and residual graphical analysis, according to the municipality and growth condition. When comparing the equations, covariance analysis indicated that there is no significant difference between the level and slope of the crown diameter equations of open growth trees and under competition in different places where data were sampled. A single equation was defined to estimate the crown diameter as a function of the diameter at breast height for this species.